Mengembangkan partisipasi warga negara dalam memelihara dan mengembangkan sistem politik Indonesia - Cholisin Cholisin (Jurnal Civics: Media Kajian Kewarganegaraan, 2009)
Political system of Indonesia is ongoing process of democratization. There are many attitude sould be performed by citizen to respond development of democracy: first, self openness to reflect weaknesses, mainly in mentality of states aparatus. Second, appreciation toward Political System of Pancasila Democracy as a manifestation of proportional and rational political attitude. Third, political participation which appropriates the rule or regulation, namely, constructive and conventional participation toward developing the order, peaceful, civilized, and prospering democracy.